3D Pictorial Structures for Multiple View Articulated Pose Estimation - Burenius, Magnus; Sullivan, Josephine; Carlsson, Stefan (2013 IEEE Conference on Computer Vision and Pattern Recognition, 2013)
We consider the problem of automatically estimating the 3D pose of humans from images, taken from multiple calibrated views. We show that it is possible and tractable to extend the pictorial structures framework, popular for 2D pose estimation, to 3D. We discuss how to use this framework to impose view, skeleton, joint angle and intersection constraints in 3D. The 3D pictorial structures are evaluated on multiple view data from a professional football game. The evaluation is focused on computational tractability, but we also demonstrate how a simple 2D part detector can be plugged into the framework.